Incorporation and solidification mechanism of manganese doped cement clinker - Yang, Nan; Li, Aihong; Liu, Qing; Cui, Yanshuai; Wang, Zhaojia; Gao, Yukun; Guo, Jianping (Frontiers in Chemistry, 2023)
Using municipal and industrial solid waste as a substitute raw material and fuel in cement rotary kiln co-processing is considered an economic and environmentally friendly alternative to the use of traditional fuels. However, the presence of heavy metals in solid waste is a growing concern in the cement rotary kiln co-processing technique. The solidification mechanism of heavy metals in cement clinker is directly related to their stabilization. Cement clinkers doped with manganese oxide (MnO2: 0.0%–5.0% wt%) were prepared in a laboratory to investigate the impacts of extrinsic Mn on cement clinker calcination. The insignificant changes in X-ray diffractometer patterns indicated that the fixed Mn had little influence on the mineral lattice structure. Raman spectra and X-ray photoelectron spectroscopy revealed the transformation of the silicate phase when the Mn dose was increased. Moreover, the satisfactory solidification ratio confirmed the incorporation of Mn in the cement clinker. These results provided evidence of the influence rule of Mn in the cement clinker calcination process. Furthermore, Raman spectroscopy showed great potential for the qualitative and semi-quantitative analysis of the cementitious materials derived from cement rotary kiln co-processing. These results will be important for the further development of green cement manufacturing technology.